Implementasi Kebijakan Penyusunan dan Penetapan Standar Pelayanan Minimal Pada Dinas Kebersihan, Pertamanan, dan Pemadam Kebakaran Kabupaten Bekasi - Yayan Rudianto (Program Studi Ilmu Administrasi Negara, Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam '45 (UNISMA) Bekasi, 2012)
Governance in general has two main functions, which are the regulation function and service function. Regulation function refers to the Law of the Republic of Indonesia Number 32/2004 of Regional Government, and the service function refers to the Law of the Republic of Indonesia Number 25/2009 of Public Service. Both of these functions have not been implemented consistently. The rules are still at odds with the rules above it, and the quality of public services is still low. The results showed that the function of the Office of Health, Landscaping, and Firefighter in implementing the regulations on minimum service standards (SPM) have not been successful. The causes are: first, the executor is not clear about the meaning of the policy implementation. Secondly, the implementers do not understand the difference with regard to the clarity of shape public policy. Third, the implementers do not understand the difference with regard to clarity and understanding sequence of policy implementation, particularly the public sector. Bekasi district government gave the task to the Office of Public Works to prepare and submit an annual public report application performance and achievement of SPM to the Minister of Home Affairs through the Governor, when it should be the task of the Office of Health, Landscaping, and Firefight